2023
DOI: 10.1158/1055-9965.epi-22-0966
|View full text |Cite
|
Sign up to set email alerts
|

Rural, Large Town, and Urban Differences in Optimal Subspecialty Follow-up and Survivorship Care Plan Documentation among Childhood Cancer Survivors

Abstract: Background: Children with cancer from rural and non-urban areas face unique challenges. Health equity for this population requires attention to geographic disparities in optimal survivorship-focused care. Methods: The Oklahoma Childhood Cancer Survivor Cohort was based on all patients reported to the institutional cancer registry and <18-years-old at diagnosis between January 1, 2005, and September 24, 2014. Suboptimal follow-up was defined as no completed oncology-related clinic visit five to seven yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…37 Thus, analysis of this relatively privileged group potentially overestimates adherence among all long-term survivors of childhood cancer, given reported disparities in accessing various aspects of survivorship care. 38 , 39 , 40 If so, these findings demonstrate an even greater need for solutions to optimize cardiovascular screening for all adult survivors of childhood cancer.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…37 Thus, analysis of this relatively privileged group potentially overestimates adherence among all long-term survivors of childhood cancer, given reported disparities in accessing various aspects of survivorship care. 38 , 39 , 40 If so, these findings demonstrate an even greater need for solutions to optimize cardiovascular screening for all adult survivors of childhood cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Our study cohort also comprises a large number of participants who identified as non-Hispanic White and were more likely to have health insurance than the general US population, among whom the proportions of uninsured adults aged 19 to 64 years ranges from 9% to 15% . Thus, analysis of this relatively privileged group potentially overestimates adherence among all long-term survivors of childhood cancer, given reported disparities in accessing various aspects of survivorship care . If so, these findings demonstrate an even greater need for solutions to optimize cardiovascular screening for all adult survivors of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy‐three percent of all survivors in remission in the Oklahoma cohort have a record in PFC. Of note, survivors without PFC were significantly more likely to be older, live in a nonurban area, and live further away from the medical center compared with survivors with PFC 33 . For population‐level treatment exposures, we downloaded data from the encrypted PFC service to a secure shared folder behind the University of Oklahoma Health Sciences firewall, accessible with log‐in only by key study personnel approved by the Institutional Review Board as part of the data and safety monitoring plan.…”
Section: Methodsmentioning
confidence: 98%
“…Of note, survivors without PFC were significantly more likely to be older, live in a nonurban area, and live further away from the medical center compared with survivors with PFC. 33…”
Section: Treatment Exposures Data Elementsmentioning
confidence: 99%
“…13 Previously identi ed disparities among adolescents and survivors from non-urban areas in survivorship care, such as optimal subspecialty follow-up and receipt of a survivorship care plan, may also in uence downstream treatment-related CVD. 14 This is particularly important for vulnerable populations, such as those from rural areas, are already at increased risk for CVRFS and CVD later in life. [15][16][17] Moreover, fragmented healthcare systems for AYA survivors and those from non-urban areas underscore the role of data standards to surmount siloed data challenges through interoperability with the ultimate goal to improve patient care.…”
Section: Introduction Page 4/22mentioning
confidence: 99%